324. Lack of Accuracy of the International Classification of Disease, Ninth (ICD-9) Codes in Identifying Patients With Encephalitis. (26th November 2018) - Samannodi, Mohammed; Hansen, Michael; Hasbun, Rodrigo
Abstract: Background: ICD-9 codes have been widely used in studies utilizing large national databases that evaluate the clinical epidemiology of encephalitis in the United States. Many studies have showed that ICD-9 codes have poor accuracy in stroke, multiple sclerosis and pulmonary fibrosis but their utility in encephalitis is unknown. Methods: Retrospective study of all adults with a discharge diagnosis of encephalitis by an ICD-9 code. The study was performed in 17 hospitals from the Memorial Hermann Hospital and Harris Health Hospital system in the Greater Houston area from March 2010 until July 2015. Medical records were reviewed and a case was considered accurately classified as encephalitis if they met the definition established by the international encephalitis consortium. Results: A total of 1, 241 cases were identified by a discharge diagnosis of ICD-9 code as having encephalitis. The most common cause identified was not having a central nervous system infection in 580 (46.7%) patients. A total of 244 (19.6%) patients were correctly identified as having encephalitis. Other causes identified were nosocomial meningitis (11.9%), community-acquired bacterial meningitis (8.1%), aseptic meningitis (5.8%), fungal meningitis (5.4%), tuberculosis (2.0%), and parasitic meningitis (0.2%). Conclusion: ICD-9 codes have poor reliability in identifying patients with encephalitis questioning the accuracy of large nationwide studies that utilize them to identify patients. Disclosures: All authors: No reported disclosures.